Landscape evolution of Dartmoor, SW England: A review of evidence-based controversies and their wider implications for geoscience. Issue 2 (April 2020) - Gunnell, Yanni
Abstract: Dartmoor's landscape has been studied for ∼200 years but is still imperfectly understood. Here we explore Dartmoor as a geoscientific incubator, focusing on why such a small portion of the Earth's surface has generated such a galaxy of diverse landscape evolution scenarios. A carousel of controversies over rock weathering, drainage evolution, the chronology and intensity of base-level changes and palaeoclimates is examined in detail. Their bearing on how we interpret the land surface are discussed, with suggestions for future investigation. By also analysing the ontological and epistemological underpinnings of the research, the review resonates with the wider history of geoscience.